Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\int \frac{x^2+1}{x^5-1}dx$$

I am unable to integrate it, nothing works. Yes, I can use partial fraction but who remembers factorization of $x^5-1$, I need a better way of doing this.

share|cite|improve this question
You don't have to "remember" the factorization of $x^5-1$. Notice that $x=1$ is a solution and use long division to see that $x^5-1=(x-1)(x^4+x^3+x^2+x+1)$. – chris Apr 14 '12 at 6:55
@chris: Long division? Geometric sum formula bro. – anon Apr 14 '12 at 6:56
@anon: That works too. It's useful to know that, in general, if you can spot a solution then long division is a way to get the factorization of the polynomial though. – chris Apr 14 '12 at 6:57
If this is homework problem, you have a cruel instructor. (Unless there is a smart way of doing this that I haven't figured out yet) – Shitikanth Apr 14 '12 at 7:13
Very cruel indeed; this results in an unholy mass of arctangents and logarithms... – J. M. Apr 14 '12 at 7:47

Take the denominator, find the 5 complex roots,one of them is 1.Descompose the denominator as: $$(x^5 - 1) = (x-1)\cdot(x-a)(x-a^*)\cdot(x-b)(x-b^*)$$ Remember that $(x-a)(x-a^*)$ is a polynomial of second degree with real coefficients. Then apply descomposition in simple (partial) fractions.

share|cite|improve this answer
+1: In case the OP or somebody else has problems finding the roots, they are the fifth primitive roots of unity: $a=e^{2\pi i/5}$, $b=e^{4\pi i/5}$. Here $$ (x-a)(x-a^*)=x^2-(a+a^*)x+aa^*=x^2-(2\cos\frac{2\pi}5)x+1. $$ Remember that $$2\cos\frac{2\pi}5=\frac{\sqrt{5}-1}2.$$ The coefficients become a bit cumbersome, but this allows the use of the common techniques of finding the indefinite integral of a rational function. – Jyrki Lahtonen Apr 14 '12 at 7:53

There's always this solution that can be used in a neighborhood of $0$ with a convergence radius of $1$ : $$ \int \frac{x^2 + 1}{x^5-1} \, dx = \int -(x^2+1) \left( \sum_{i=0}^{\infty} x^{5i} \right) \, dx = \sum_{i=0}^{\infty} \frac{x^{5i+1}}{5i+1} + \sum_{i=0}^{\infty} \frac{x^{5i+3}}{5i+3} $$ but unless that's what you were expecting, I don't thing it's worth very much. Note that the expansion alpha.Debi was suggesting will probably involve at some point the integration of terms of the form $1/(x-a)$, which will most probably bring up logarithms, which are not well-behaving (in the sense that they are multivalued functions over $\mathbb C$) for integration with respect to a path (even though it does work, I'm just mentioning "there's a point to notice there"). Perhaps the solution in terms of logarithms obtained in this fashion is equivalent to this one in a neighborhood of $0$.

Hope that helps,

share|cite|improve this answer
But in the descomposition I suggested , we forget the complex numbers after multiplying (x-a)(x-conjugate a),then we continue only in the way of integral of simple fractions all with real coefficients. – alpha.Debi Apr 14 '12 at 7:51

I'd like to point out that you can factorize $x^5 -1$ quite easily by observing that you are actually finding the fifth roots of 1: $$x =\sqrt[5]{1} = e^{2\pi i k/5}$$ So that as @alpha.Debi pointed out, factorizing the denominator may be long, but is quit straight forward.

share|cite|improve this answer

For these cyclotomic denominators, one can get an answer pretty fast by factoring into roots of unity. Let $\omega_k=e^{i\theta_k}=\cos\theta_k+i\sin\theta_k$, where $\theta_k=2\pi k/5$. Then $$\frac{x^2+1}{x^5-1}=\frac{x^2+1}{\prod_{k=0}^4(x-\omega_k)}=\sum_{k=0}^4\frac{A_k}{x-\omega_k}$$ Obeserving that $\omega_k^{-k}=\omega_k^{5-k}$ and applying L'Hopital's rule a couple of times, $$\begin{align}\lim_{x\rightarrow\omega_k}\frac{(x^2+1)(x-\omega_k)}{x^5-1} & =\lim_{x\rightarrow\omega_k}\frac{(x^2+1)(1)}{5x^4}=\frac15\left(\omega_k^{-2}+\omega_k\right) \\ & =\lim_{x\rightarrow\omega_k}\sum_{j=0}^4\frac{A_j\left(x-\omega_k\right)}{x-\omega_j}=\sum_{j=0}^4A_j\delta_{kj}=A_k\end{align}$$ Then $$\begin{align}\int\frac{x^2+1}{x^5-1}dx & =\sum_{k=0}^4A_k\int\frac{dx}{x-\omega_k}=\sum_{k=0}^4\frac15\left(\omega_k^{-2}+\omega_k\right)\ln\left(x-\omega_k\right)+C_1 \\ & =\sum_{k=0}^4\left(\cos2\theta_k+\cos\theta_k-i\sin2\theta_k+i\sin\theta_k\right)\ln\left(x-\cos\theta_k-i\sin\theta_k\right)+C_1 \\ & =\sum_{k=0}^4\left(\cos2\theta_k+\cos\theta_k-i\sin2\theta_k+i\sin\theta_k\right)\left\{\frac12\ln\left(x^2-2x\cos\theta_k+1\right)+i\,\text{atan2}\left(-\sin\theta_k,x-\cos\theta_k\right)\right\}+C_1 \\ & =\sum_{k=0}^4\left(\cos2\theta_k+\cos\theta_k-i\sin2\theta_k+i\sin\theta_k\right)\left\{\frac12\ln\left(x^2-2x\cos\theta_k+1\right)+i\,\text{atan2}\left(x-\cos\theta_k,\sin\theta_k\right)\right\}+C \\ & = \sum_{k=0}^4\left\{\frac12\left(\cos2\theta_k+\cos\theta_k\right)\ln\left(x^2-2x\cos\theta_k+1\right)+\left(\sin2\theta_k-\sin\theta_k\right)\tan^{-1}\left(\frac{x-\cos\theta_k}{\sin\theta_k}\right)\right\}+C\end{align}$$ because the imaginary parts cancel out above. The $k=0$ term is just $\frac25\ln|x-1|$ and the $k=4$ term is a copy of the $k=1$ term, just as the $k=3$ term is a copy of the $k=2$ term. So substituting in the values of the trig functions above and simplifying, we get $$\begin{align}\int\frac{x^2+1}{x^5-1}dx=\frac25\ln|x-1| & -\frac1{10}\ln\left(x^2+\frac{1-\sqrt5}2x+1\right) \\ & +\frac{\sqrt{10-2\sqrt5}\left(1-\sqrt5\right)}{20}\tan^{-1}\left(\frac{4x-\sqrt5+1}{\sqrt{10+2\sqrt5}}\right) \\& -\frac1{10}\ln\left(x^2+\frac{1+\sqrt5}2x+1\right) \\ & -\frac{\sqrt{10+2\sqrt5}\left(1+\sqrt5\right)}{20}\tan^{-1}\left(\frac{4x+\sqrt5+1}{\sqrt{10-2\sqrt5}}\right)+C\end{align}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.